Daily field checking list by Walter Rosene, April 19, 1932 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 19, 1932. This checklist was used by Walter Rosene to record birds sighted enroute from Ogden to Rockwell City. Plustek--flatbed